2006
DOI: 10.1063/1.2209170
|View full text |Cite
|
Sign up to set email alerts
|

Pressure- and temperature-induced phase transition in the B–C system

Abstract: A direct transformation from the g-BC1.6 phase to a diamondlike BC1.6 phase was obtained in a diamond-anvil cell at high temperature, 2230±140K, and high pressure, 45GPa. Such a transition has not been observed in the B–C system before. The recovered samples were examined using both synchrotron-based x-ray diffraction and confocal micro-Raman spectroscopy at ambient conditions. The lattice parameter of the diamondlike phase (3.5745Å) is close to that of diamond. The measured visible laser-excited Raman spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The HPHT conditions of the transition of the graphitic BC x phase to another phase are also disputable: phase transitions were detected above 35 GPa in Refs. [16][17][18]21 ; and was not observed in the BC x system (1.6 < x ≤ 3) at pressures of 20 GPa 15 , 19 GPa 17 , and 24 GPa (Ref. 16 and this study).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The HPHT conditions of the transition of the graphitic BC x phase to another phase are also disputable: phase transitions were detected above 35 GPa in Refs. [16][17][18]21 ; and was not observed in the BC x system (1.6 < x ≤ 3) at pressures of 20 GPa 15 , 19 GPa 17 , and 24 GPa (Ref. 16 and this study).…”
Section: Introductionmentioning
confidence: 98%
“…[16][17][18]21 ; and was not observed in the BC x system (1.6 < x ≤ 3) at pressures of 20 GPa 15 , 19 GPa 17 , and 24 GPa (Ref. 16 and this study). Contrary to abovementioned results, the authors of Ref.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent experiments on graphitelike BC 3 showed that at 20 GPa and 2200 K in a multianvil press, the phase decomposes into the mixture of boron-doped diamond ($1:8 at% of boron) and boron carbide [9]. Very recently, phase segregation of graphitelike BC 1:6 into a mixture of diamond, boron carbide, and elemental boron was observed in a diamond anvil cell at 45 GPa and 2230 K [10]. Hence, all previous attempts to synthesize diamondlike B-C phases with boron concentration higher than $2 at% have failed.…”
mentioning
confidence: 99%